2014
DOI: 10.1007/s40093-014-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vegetable wastes recycled for vermicomposting and its response on yield and quality of carrot (Daucus carota L.)

Abstract: Background Vegetable crops generate a large amount of crop residues after harvesting of economic part. These potentially nutritious residues are soft, succulent and easily decomposable and instead of disposing or damping, it can be used as source of organic residues for utilizing the embedded nutrients through compost production. In the present study, diverse vegetable wastes were recycled for vermicomposting and their effects were evaluated in field experiments in organic carrot production. Results The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…While the lowest (49.5 g) fresh root weight was recorded at the control (Table 4). Chatterjee et al (2014) on their study on evaluation of vegetable wastes recycled for vermicomposting and its response on yield and quality of carrot reported that vermicompost from wastes from non-legume and legume family at 2:1 ratio resulted in high root weight. Rani and Mallareddy (2006) in their study on effect of different organic manures and inorganic fertilizers on growth, yield and quality of carrot documented that maximum fresh carrot weight (55.23 g) was significantly higher with integration of neem cake /4t ha -1 / and half the recommended dose of NPK treatments.…”
Section: Total Fresh Biomass (G/plant) and Fresh Root Weight (G/plant)mentioning
confidence: 99%
“…While the lowest (49.5 g) fresh root weight was recorded at the control (Table 4). Chatterjee et al (2014) on their study on evaluation of vegetable wastes recycled for vermicomposting and its response on yield and quality of carrot reported that vermicompost from wastes from non-legume and legume family at 2:1 ratio resulted in high root weight. Rani and Mallareddy (2006) in their study on effect of different organic manures and inorganic fertilizers on growth, yield and quality of carrot documented that maximum fresh carrot weight (55.23 g) was significantly higher with integration of neem cake /4t ha -1 / and half the recommended dose of NPK treatments.…”
Section: Total Fresh Biomass (G/plant) and Fresh Root Weight (G/plant)mentioning
confidence: 99%
“…Chatterjee et al [37] recycled different vegetable wastes for vermicomposting and found that among different vegetable wastes vermicompost prepared from non-legume and legume waste at 2:1 ratio emerged as best growth medium in terms of superior yield and quality attributes with maximum root length (19.26 cm), root volume (73 cm 3 ) and root weight (68.43 g) as well as beta carotene (3.28 mg 100 g -1 ) and TSS content of the carrot root (7.96 °Brix). The positive response of vermicompost on plant growth and yield was not only due to the available nutrients but also due to the availability of plant growth influencing materials, such as growth regulators, humic acids produced by the microbial population resulting from earthworm activity.…”
Section: Effect Of Recycled Organic Wastes On Crop Growthmentioning
confidence: 99%
“…The results revealed that combination of composting followed by vermicomposting reduced the overall time required for composting and accelerate the composting of lignocellulosite wastes besides producing a nutrient enrich compost product. Chatterjee et al [37] recycled different vegetable wastes for vermicomposting and found that among different vegetable wastes, substrate combining mixture of non-legume and legume wastes at 2:1 emerged best substrate considering the nutrient contents, C/N ratio, earthworm biomass and vermicompost recovery (Tables 5-8) [57][58][59][60][61].…”
Section: Composting By Involving Earthworms-an Alternativementioning
confidence: 99%
“…Due to the application of vermicompost in the soil, it functions as a cement like agent between soil particles and water holding clay to bind together; as a result, the crumb structures of the soil produce resistant against soil erosion and binds micronutrient metal ions in the soil to check leaching out from surface soils. It also contains humic acids, N-fixing, and P-solubilizing bacteria, plant growth stimulating substance such as auxins, cytokinins, and gibberellins (Chatterjee et al 2014;Najar et al 2015). Sometimes, potato produces in Bangladesh is not good quality enough in respect of starch content, reducing sugar content, antioxidant, and polyphenol content.…”
Section: Introductionmentioning
confidence: 99%